Competition and Educational Quality: Evidence from The Netherlands - Elbert Dijkgraaf; Raymond H.J.M. Gradus; Matthijs de Jong (Tinbergen Institute, 2009)
Ample evidence is available for the effect of competition on educational quality as only a few countries allow large scale competition. In the Netherlands free parental choice is present since the beginning of the 20th century, which can be characterized as a full voucher program with 100% funding. Based on panel data for the Netherlands we show that there is a relation between competition and educational outcomes in secondary education, but that it is negative and small. This effect is larger for small and medium sized schools and for schools which do not have a Protestant or Catholic denomination.
Keywords: H70; I20; 330; Competition; Private Schools; Scale; Quality; Secondary Education; Allgemeinbildende Schule; Wettbewerb; Privatschule; Bildungsniveau; Niederlande